PENCEGAHAN INFORMASI BOHONG PADA MEDIA SOSIAL: PERSPEKTIF AGAMA-AGAMA DI INDONESIA - Prasetyo, Arienda Addis; Sari, Ramadanita Mustika (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2021)
The existence of an everywhare internet connection, the use of the smartphone, and social media, the community with easy access and receive information, social media as mass information media has two sides of the impact of different.Because of the convenience of social media in presenting information to the user, be as a trigger easy it is the community in obtaining news or information.Information have diverse namely uncertainty, character , Knowledge, Ambiguity,Ridanden, Indetermination, and The System that Relies, to addressing that religious institutions as facilitator in the formation of moral made priority in information filter that is not true with the use of studies that derived from the teachings of every religion. Religion it becomes a necessity that must be met, religion began to be perceived as something that gives value and meaning in life, then religion becomes institutionalized in society be religious as one of the institutions of social. Therefore, the religious institutions have to earn the trust of the public in a democracy such as political freedom, honesty, public approval, competition and legitmasi. Preventing exposure of information lie in self, family, society and nation state with the way the back hold firmly the teachings of each religion, the stronger we hold fast to the teachings of the religion, the more we afraid of doing “the hoax “ itself because the information is a lie it is not justified in the teachings of every religion. Writing methods with the methods of interpretation using a thematic approach. The method of study used in the search data is a literature study (library research) as well as interviews with respondents who related. Analysis the study was conducted using analysis descriptive qualitative. Keywords: Information, Institutions Religion, The Role Of Religion